Innovative Approaches to Hr Management is the Objective Need of Modern Hr Management - Erkinovna, Ahtamova Mohigul; Davlat, Boboqulov (Researchparks Publishing, 2023)
Innovative approaches to personnel management are essential for modern HR management to meet the evolving needs and expectations of the modern workforce. This article identifies various innovative approaches, including flexible work arrangements, employee development programs, and performance management systems, and explores their benefits and limitations for both employees and organizations. The article also examines the challenges of implementing these approaches and suggests future research directions. The findings suggest that innovative personnel management approaches can improve employee satisfaction, motivation, and productivity, as well as enhance organizational performance and competitiveness. However, implementation can also be challenging due to factors such as resistance to change and lack of resources. In conclusion, this article highlights the importance of innovative approaches to personnel management in modern HR management and offers insights into their potential benefits and challenges.